Full structural ensembles of intrinsically disordered proteins from unbiased molecular dynamics simulations - Utsab R. Shrestha (Nature Portfolio, 2021)
Shrestha et al. show that enhancing the sampling using Hamiltonian replica exchange molecular simulation (HREMD) leads to accurate unbiased ensembles of intrinsically disordered proteins. They find that standard molecular simulation cannot reproduce small-angle scattering data as well as HREMD, highlighting the utility of the suggested approach.